Precarious work and chronic disease: lessons learned from the US national agricultural worker survey (1999–2020) - Iglesias-Rios, Lisbeth; Li, Kexin; Handal, Alexis J.; Wang, Lu (Frontiers in Public Health, 2025)
BackgroundPrecarious employment and labor exploitation in farmworkers is historical and pervasive in the United States.MethodsWe analyzed cross-sectional data from the National Agricultural Worker Survey (1999–2020, NAWS) among 46,910 farmworkers. A multidimensional precarious employment score (PES) was developed using work indicators and cardiovascular risk factors and cardiovascular disease (CVD). Analysis included: (1) Poisson regression model with LASSO for key predictor selection across three health outcomes; (2) PES construction to track employment conditions over time; and (3) subgroups analyses to assess disparities and trends in employment precarity.ResultsWomen showed no reduction in PES over time. Indigenous farmworkers [mean (M) = 0.52, 95% CI: 0.50 to 0.53; difference from reference (δM) = 0.07, 95% CI: 0.05 to 0.08] and those working with labor contractors (M = 0.5, 95% CI: 0.48 to 0.52; δM = 0.05, 95% CI: 0.04 to 0.07) showed a consistently higher PES, but their declines [Indigenous: change (ΔM) = −0.05, 95% CI: −0.09 to 0; labor contractors: ΔM = −0.08, 95% CI: −0.12 to −0.05) were smaller.ConclusionsWithin this precarious workforce there were differences in PES and chronic disease. Biosocial data is needed to better understand the pathways of how precarious employment impacts the health of this workforce.